2019
DOI: 10.3390/en12030383
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Process for Production of Calophyllum Inophyllum Biodiesel with Electromagnetic Induction

Abstract: A novel method as proposed in the production of Calophyllum inophyllum biodiesel has been investigated experimentally. This study reports the results of biodiesel processing with electromagnetic induction technology. The applied method is aimed to compare the results of Calophyllum inophyllum biodiesel processing among conventional, microwave and electromagnetic induction. The degumming, transesterification, and esterification process of the 3 methods are measured by stopwatch to obtain time comparison data. C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 63 publications
0
4
0
1
Order By: Relevance
“…Kurniati et al [46] propose an advanced electromagnetic induction technology that provides a fast and easy way to produce biodiesel. This method has the following advantages: it increases the reaction speed, it improves the separation process, it increases production, and it reduces production time and costs compared to conventional or microwave induction methods.…”
Section: Biodiesel Productionmentioning
confidence: 99%
“…Kurniati et al [46] propose an advanced electromagnetic induction technology that provides a fast and easy way to produce biodiesel. This method has the following advantages: it increases the reaction speed, it improves the separation process, it increases production, and it reduces production time and costs compared to conventional or microwave induction methods.…”
Section: Biodiesel Productionmentioning
confidence: 99%
“…Inductive heating is advantageous in this process because a rapid and uniform heating of the biomass and catalyst is important for product quality. Compared to a conventional heating process, the authors found that a higher quality of bio-oil with a higher yield of aromatic hydrocarbons and a lower oxygen content is obtained in a process with RF heating [ 41 ].…”
Section: Reviewmentioning
confidence: 99%
“…The obtained coefficient of variation (CV) value of 1.27% indicates a good model. For a good model, the CV must be less than 10% (Kurniati et al, 2019).…”
Section: Design Of Experiments and Statistical Analysis By Response S...mentioning
confidence: 99%